Testing climate and agriculture policy against future scenarios - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Since 2010, the team has built regional scenarios for East and West Africa, South and Southeast Asia, Central America and the Andes. Recently their focus has shifted to helping national officials develop their own scenarios to improve specific policies. That work is now starting to pay off in scenario-guided planning.